Place of clinical evaluation in the identification of obstructive coronary arteries lesions in patients with stable coronary artery disease: Part II - A. N. Sumin (Российский кардиологический журнал, 2019)
The article discusses the main stages of the diagnostic process (clinical evaluation, determination of pre-test probability, non-invasive tests). In this part of the review, two new approaches of non-invasive tests are considered. First one — with a focus on non-invasive determination of anatomical changes in the coronary bed using multispiral computed tomography-angiography, second one — with the calculation of the post-test probability of obstructive coronary artery disease. In general, this review will help researchers and clinicians about in better understanding of modern diagnostic capabilities in identifying of obstructive coronary artery disease.